Silver Bullet Speaks with Dorothy Denning. - McGraw, Gary (IEEE Security and privacy : building confidence in a networked world)
Gary McGraw speaks with Dorothy Denning in a wide-ranging conversation that covers teaching computer security to the Big Sur Power Walk.